Interakcje pomiędzy kalusem trzech genotypów Abies alba a grzybami o różnym statusie ekologicznym - Nawrot-Chorabik, Katarzyna; Jankowiak, Robert (Leśne Prace Badawcze, 2010)
Callus cultures derived from three Abies alba genotypes were co-cultivated with several fungi of different ecological status. Growth of Heterabasidion parviporum , Ophiostoma piceae and Pesotum sp. was stimulated, whilst Heterobasidon abietinum and Geosmithia sp. were unaffected by the presence of callus (statistical analyses for these 2 fungi gave no difference and a marginally-significant different respectively). Fir callus inhibited the growth of Pesotum fragrans and Rizosphaera macrospora . Otherwise, there were significant differences between the callus genotypes with respect to the growth of fungi and colonization of fir callus. Fungi H. abietinum , O. piceae , R. macrospora and Geosmithia sp. first colonized callus belonging to genotype G6. In contrast, fungal species: P. fragrans , Pesotum sp., Geosmithia sp. and H. parviporum quickly colonized callus derived from the genotype G5. Across all genotypes, callus was colonized in the shortest period of time by the fungus H. parviporum (causing callus necrosis after 6-9 days), the slowest was Pesotum sp. (causing callus necrosis after 60-81 days). The importance of these results regarding pathogenicity and behaviour in vivo of these fungi is discussed.